Wintertime photochemistry in Beijing: Observations of ROx radical concentrations in the North China Plain during the BEST-ONE campaign - Tan, Z. F.; Rohrer, F.; Lu, K. D.; Ma, XF; Bohn, B.; Broch, S.; Dong, H. B.; Fuchs, H.; Gkatzelis, G; Hofzumahaus, A.; Holland, F.; X. Li; et al. (Atmos. Chem. Phys., 2018)
The first wintertime in-situ measurements of hydroxyl (OH), hydroperoxy (HO2) and organic peroxy (RO2) radicals (ROx=OH+HO2+RO2) in combination with observations of total reactivity of OH radicals, kOH in Beijing are presented. The field campaign “Beijing winter finE particle STudy – Oxidation, Nucleation and light Extinctions” (BEST-ONE) was conducted at the suburban site Huairou near Beijing from January to March 2016. It aimed to understand oxidative capacity during wintertime and to elucidate the secondary pollutants formation mechanism in the North China Plain (NCP). OH radical concentrations at noontime ranged from 2.4×106cm−3 in severely polluted air (kOH~27s−1) to 3.6×106cm−3 in relatively clean air (kOH~5s−1). These values are nearly two-fold larger than OH concentrations observed in previous winter campaign in Birmingham, Tokyo, and New York City. During this campaign, the total primary production rate of ROx radicals was dominated by the photolysis of nitrous acid accounting for 46% of the identified primary production pathways for ROxradicals. Other important radical sources were alkene ozonolysis (28%) and photolysis of oxygenated organic compounds (24%). A box model was used to simulate the OH, HO2 and RO2 concentrations based on the observations of their long-lived precursors. The model was capable of reproducing the observed diurnal variation of the OH and peroxy radicals during clean days with a factor of 1.5. However, it largely underestimated HO2 and RO2 concentrations by factors up to 5 during pollution episodes. The HO2 and RO2 observed-to-modeled ratios increased with increasing NO concentrations, indicating a deficit in our understanding of the gas-phase chemistry in the high NOxregime. The OH concentrations observed in the presence of large OH reactivities indicate that atmospheric trace gas oxidation by photochemical processes can be highly effective even during wintertime, thereby facilitating the vigorous formation of secondary pollutants.